Rapid method for screening of both calcium and magnesium chelation with comparison of 21 known metal chelators - Konečný, Lukáš; Lomozová, Zuzana; Karabanovich, Galina; Roh, Jaroslav; Vávrová, Kateřina; Mladěnka, Přemysl (Journal of biological inorganic chemistry, 2024)
Chelation is the rational treatment modality in metal overload conditions, but chelators are often non-selective and can, hence, cause an imbalance in the homeostasis of physiological metals including calcium and magnesium. The aim of this study was to develop an affordable, rapid but sensitive and precise method for determining the degree of chelation of calcium and magnesium ions and to employ this method for comparison on a panel of known metal chelators. Spectrophotometric method using o-cresolphthalein complexone (o-CC) was developed and its biological relevance was confirmed in human platelets by impedance aggregometry. The lowest detectable concentration of calcium and magnesium ions by o-CC was 2.5 μM and 2 μM, respectively. The indicator was stable for at least 110 days. Four and seven out of twenty-one chelators strongly chelated calcium and magnesium ions, respectively. Importantly, the chelation effect of clinically used chelators was not negligible. Structure-activity relationships for eight quinolin-8-ols showed improvements in chelation particularly in the cases of dihalogen substitution, and a negative linear relationship between pKa and magnesium chelation was observed. Calcium chelation led to inhibition of platelet aggregation in concentrations corresponding to the complex formation. A novel method for screening of efficacy and safety of calcium and magnesium ion chelation was developed and validated.
Keywords: trombocyty; hořčík; Platelet; vápník; chelátory; Chelator; Depletion; Calcium; preklinické hodnocení léčiv; vztahy mezi strukturou a aktivitou; Humans; Magnesium; Methodology; Drug Evaluation, Preclinical; agregace trombocytů; Chelating Agents; Platelet Aggregation; Blood Platelets; Selectivity; Structure-Activity Relationship; lidé